2010
DOI: 10.1590/s0034-89102010000600003
|View full text |Cite
|
Sign up to set email alerts
|

Atividade física e sedentarismo em escolares da rede pública e privada de ensino em São Luís

Abstract: OBJECTIVE:To analyze factors associated with physical activity and the mean time spent in some sedentary activities among school-aged children. METHODS:A cross-sectional study was carried out in a random sample of 592 schoolchildren aged nine to 16 years in 2005, in São Luís, Northern Brazil. Data were collected by means of a 24-Hour Physical Activity Recall Questionnaire, concerning demographic and socioeconomic variables, physical activities practiced and time spent in certain sedentary activities. Physical … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
16
0
26

Year Published

2013
2013
2020
2020

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 46 publications
(46 citation statements)
references
References 21 publications
4
16
0
26
Order By: Relevance
“…Com relação ao local de desenvolvimento da pesquisa, encontrou-se nas regiões Sul, Sudeste e Nordeste o maior número de estudos, sendo 41,6% (n=13) deles conduzidos no Sul (12)(13)(14)(15)(16) ; 41,6% (n=13) no Nordeste (17)(18)(19)(20)(21) ; seguidos de 12,8% (n=4) no Sudeste (22)(23)(24) e 3,1% (n=1) realizados com amostragens das regiões Sudeste e Sul (25) . Não foram encontrados estudos que tenham envolvido adolescentes das regiões Centro-Oeste e Norte, em função dos limites estabelecidos pelos critérios de inclusão.…”
Section: Resultsunclassified
“…Com relação ao local de desenvolvimento da pesquisa, encontrou-se nas regiões Sul, Sudeste e Nordeste o maior número de estudos, sendo 41,6% (n=13) deles conduzidos no Sul (12)(13)(14)(15)(16) ; 41,6% (n=13) no Nordeste (17)(18)(19)(20)(21) ; seguidos de 12,8% (n=4) no Sudeste (22)(23)(24) e 3,1% (n=1) realizados com amostragens das regiões Sudeste e Sul (25) . Não foram encontrados estudos que tenham envolvido adolescentes das regiões Centro-Oeste e Norte, em função dos limites estabelecidos pelos critérios de inclusão.…”
Section: Resultsunclassified
“…Such findings in the 'Health and Physical Activity' realm for boys may be due to the existing different gender roles in Brazilian society. According to Oliveira et al 18 , boys' participation in intense physical activities and sports is more valued at a very early age, while social stimulus is lower among girls for this practice, with a greater focus on household chores and games that involve taking care of their home, manual activities, among others. Salles-Costa et al 19 also identified the presence of gender patterns in sports practice by administrative staff of a public university located in the city of Rio de Janeiro, noting the greater male participation in collective physical activities such as soccer, volleyball and tennis, and females more involved in individual activities (gymnastics, dances, walks).…”
Section: Discussionmentioning
confidence: 99%
“…Podemos justificar essa análise de comportamento, uma elevada exposição às telas entre escolares de escolas particulares. Isso pode ser consequência de os estudantes de escolas privadas terem mais acesso aos avanços tecnológi-cos, como os elétricos e eletrônicos e, assim, ficarem mais tempo em uso desses equipamentos 19 . Um dos métodos mais utilizados para a manutenção de um constante nível de flúor no meio bucal é o creme dental.…”
Section: Discussionunclassified